“Diseño e implementación de una máquina picadora de materia orgánica en el campus ceasa ubicada en el sector de Salache” - Lema Jami, Willington Joel (2023)
This titling project aims to solve the problem that exists on the CEASA campus of the Technical University of Cotopaxi, due to the fact that organic material resulting from the pruning of different types of plants is chopped manually, this process takes too long due to which are about 400 kg of pruned organic matter to obtain a very small chopped material for the compost process, for which the objective of our project is to design and implement an organic matter chopping machine that allows chopping the material in a short time and resulting in adequate sizes for the compost, in the same way helping the chopped daily organic load to be greater, this machine contains blades that are attached to a disc that helps to chop the organic material, which passes into a chamber where they are housed a 9 series of hammers which hit the material and crushes it to then fall into a perforated mesh which selects the material with a small dimension, the material that does not have the proper size will continue to be hit by the hammers until the size is obtained to be able to exit through the mesh and later by the output tray.